Inovasi Pembelajaran Matematika Dengan Model Discovery Learning Pada Kurikulum Merdeka - Anggita Cahya Widyaningrum; Suparni Suparni (Prodi Pendidikan Matematika FKIP Universitas HKBP Nommensen, 2023)
This article discusses the innovation of learning mathematics with the discovery learning model in the independent curriculum. Merdeka Belajar is a new policy program of the Ministry of Education and Culture of the Republic of Indonesia (Kemendikbud RI) which was proclaimed by the Minister of Education and Culture of the Republic of Indonesia Advanced Indonesian Cabinet. The essence of freedom of thought must be preceded by teachers before they teach it to students. One of the quality learning models to be applied to mathematics learning in the independent curriculum is the discovery learning model. Discovery learning is a process for understanding a concept from material actively and independently to then obtain a conclusion. In this method, the teacher does not actively explain the material to students. This study uses a type of qualitative research, namely by collecting data in the form of words.